Unanticipated change in access site and anesthetic considerations for transcarotid transcatheter aortic valve implantation procedure: A case report (Indian Journal of Case Reports, 2025)
A 76-year-old man was admitted to our hospital due to his symptomatic severe aortic stenosis. With the high risk of open surgery due to comorbidities, transcatheter aortic valve implantation (TAVI) was selected after an in-depth discussion between the heart team and the patient. Since the traditional transfemoral access route was not appropriate due to severe calcifications out of proportion to computed tomography imaging, the access was changed to the left carotid route intraoperatively. A 24.5 mm Myval OCTOCAR valve was successfully implanted without any complications. The patient significantly improved postoperatively without any major cerebral and cardiovascular adverse events. TAVI through the carotid artery is thus feasible, safe, and effective in such unanticipated conditions.